Prevalence of Malnutrition among 1-36 Month Old Children Hospitalized at Imam Ali Hospital in Zahedan - Fereshteh Ghaljaei; Mahin Nadrifar; Mahnaz Ghaljeh (Iran University of Medical Sciences, 2009)
Background and Aim : Malnutrition is one of the important health problems throughout the world, particularly in developing countries, having undesirable effects on mental and physical health of children. It is an underlying factor for infection and an important cause of children mortality in these countries. The aim of this study was to determine the prevalence of malnutrition among hospitalized children aged 1-36 months at Imam Ali Hospital in Zahedan.   Material and Method : This descriptive analytical study was conducted on 360 hospitalized children aged 1-36 months, between June and November 2005. Data were collected through measurement of weight and height, and questionnaire was completed by interviewing children's parents. The authors declare that they have no conflict of interests.   Results: Nutritional status of the subjects was evaluated according to the weight- for age, weight- for height, and height- for age (Waterlow's classification) based on which.height, based on which the prevalence of malnutrition were 68.6%, 60.1%, and 38.4%, respectively. Malnutrition in children had statistically significant association with birth weight, mother job, and duration of breast feeding (P<0.05). Malnutrition increased among children in rural areas, low birth weight ones, those whose mothers were housewives, with short duration of breast feeding, and late beginning of complementary nutrition. Conclusion : regarding high prevalence of malnutrition among hospitalized children and its association with the above mentioned variables, measures such as increasing parents' awareness and literacy, constancy of breast feeding until the age of 2, starting complementary nutrition in due course, promoting complementary nutrition in due course, promoting economic, social, and health status of families, and preventing infections diseases- particularly gastroenteritis are recommended.